Bun-yat al-Manhâj Syibhu al-Muwâziyah li Qismi Ta’lîmi al-Lughati al-Arabiyyati bi Jâmi’ati Maulânâ Mâlik Ibrâhim al-Islâmiyati al-Hukûmiyati Mâlang: The Semi-Parallel Curriculum Structure for the Arabic Language Teaching Department at The State Islamic University of Maulana Malik Ibrahim Malang - Hadi, Nurul; Asrori, Imam; Hamid, M. Abdul (Center of Language Development, Institut Agama Islam Negeri Madura, 2023)
The frequent changes in government policies regarding higher education curricula pose a problem for many universities. One recent policy that has caused issues is the